PEMBERIAN KJP ( KARTU JAKARTA PINTAR) STUDI KASUS PADA SMP 120 JAKARTA - Susanti Susanti; Dirgahayu Erri (Yayasan Akrab Pekanbaru, 2019)
Education is a comprehensive thing and involves many systematic aspects. Therefore one of the determining factors for the success of our education program. At present there is the recruitment of students who get the Jakarta Smart Card (KJP). This study aims to determine the extent of the effectiveness of the procurement of smart jakarta program in SMP Negeri 120. The sample in the study was all student in the junior high school. The results of the study showed that the card-giving program was very effective, even though there were students who refused the card.